1996
DOI: 10.1007/s002040050335
|View full text |Cite
|
Sign up to set email alerts
|

Change of embryotoxic susceptibility to di- n -butyltin dichloride in cultured rat embryos

Abstract: Di-n-butylin dichloride (DBTCl), which is commonly used as heat and light stabilizer for polyvinyl chloride (PVC) plastics, is a teratogen in vivo. In the present study, the toxic effects were investigated of DBTCl on cultured rat embryos during three different stages of organogenesis. Rat embryos explanted on gestational day (GD) 8.5, GD 9.5, and GD 11.5 were cultured for 68, 46, and 48 h and were exposed to a range of DBTCl concentrations for the first 24, 46, and the last 46 h of culture, respectively. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In the rat embryo culture, DBTCl induces the craniofacial defects in the embryo from GDs 8.5 and 9.5, but not from GD 11.5 (Ema et al, 1996). In the normal rat development, the craniofacial primordium is already formed in a 15-20 somite embryo on GD 9.5-10 (Butcher, 1929;Kaufman, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In the rat embryo culture, DBTCl induces the craniofacial defects in the embryo from GDs 8.5 and 9.5, but not from GD 11.5 (Ema et al, 1996). In the normal rat development, the craniofacial primordium is already formed in a 15-20 somite embryo on GD 9.5-10 (Butcher, 1929;Kaufman, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…DBT appears to cause a variety of birth defects in rats and to disrupt normal embryonic development (Ema et al, 1996; Noda et al, 1993). Thymus atrophy and pancreatitis are consequences of DBT exposure in rats (Merkord et al, 1997; Pieters et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ema et al [35,36] showed a direct correlation between the length of exposure to DBT and the onset of defects in developing rat embryos. Another study described toxic effects that cause anomalies in the development of testicles in mice [37].…”
Section: Evidence Of the Toxic Effects Of Tbtmentioning
confidence: 99%